The Creation of EYL Textbooks in Indonesia: An Interview Study on EFL Teachers’ Perceptions - Arida Mufidah; Mustofa, Mutmainnah; Ubaidillah, M. Faruq (Universitas Nahdlatul Ulama Surabaya, 2022)
Textbooks are a type of teaching material. Textbooks used in classrooms must have gone through an evaluation process based on standards for textbook creation. However, various problems arise in the production of textbooks, especially English textbooks for grades 1-3. This study used a case study to find out what information is used by EFL teachers for low grades textbook creation and the causes of material gaps in in the textbook situated in an elementary school in Malang, East Java, Indonesia. Participants in this study were 6 teachers who had created English textbooks for their EYL classes. Data were collected through interviews. Semi-structured interviews were used to address questions and explore topics of interest. From the interviews, there were 3 answers to the first research question, which is what teachers use when creating textbooks for lower grade, those are; 1) worksheets, 2) the combination of books and worksheeet and 3) Internet. There were 4 main answers to the second research question regarding the difficulties or obstacles experienced by teachers in creatingcreating the English books. Those are; 1) standart in creating tetxtbooks, 2) time allocation in creating books, 3) feedback in creating textbooks, and 4) English as local content.